ANALISIS DAN PERANCANGAN APLIKASI E-LEARNING BERBASIS LEARNING MANAGEMENT SYSTEM (LMS) MOODLE DI PROGRAM STUDI TEKNIK PERTANIAN UNIVERSITAS SAM RATULANGI - Farri K. Komendangi; R. Molenaar; L. Lengkey (Universitas Sam Ratulangi, 2017)
ABSTRACT Currently the teaching and learning process in the Agricultural Engineering Study Program at the University of Sam Ratulangi can said as still conventional. The learning process between students and lecturers can only be made by physical classroom meeting activities with limited time available. Moreover, if a meeting between students and lecturers not happen, then the learning process will not be able to take place. Or if a lecturer cannot come to class due to some reasons then the subject materials cannot be delivered. These lead to an inefficient learning process, because of the limitations of time and place. Therefore, to address the problems outlined above, providing a system of electronic based learning (e-learning) using LMS Moodle considered as the solution of the existing problems. E-learning is proposed as a complement to the existing conventional learning system at the Agriculture Engineering Study Prograam, Sam Ratulangi University. The purpose of this study was to analyze and design of an appropriate application of elearning learning for Agricultural Engineering Study Program at Sam Ratulangi University. The results show that the functionality of the system is able to fulfill the requirement in supporting the e-learning process. The results of the questionnaire distributed to lecturers and students suggested that more thanÂ 80% of respondents said the system is very helpful to support the learning activities, as well as more than 84% of respondents are interested in implementing the e-learning system.